The dynamic interplay of opposites in zoroastrianism - Florentin Smarandache (Journal of Fuzzy Extension and Applications)
This exploration addresses some aspects of Zoroastrianism, examining how the ancient Persian belief system aligns with the dynamic and indeterminate principles of  Fuzzy, Neutrosophic, and MultiAlist systems. Zoroastrianism, rooted in the eternal struggle between good and evil, light and darkness, exhibits parallels with Neutrosophy's acknowledgment of indeterminacy, incompleteness, and the dynamic interplay of opposites. The prophet Zarathustra's vision of a neutrosophic God challenges conventional notions of divine attributes, emphasizing a dynamic and evolving universe. Before investigating these vague areas, the concept of unclear conceptual borders is explored, emphasizing the indeterminacy and imprecision inherent in defining opposites or partially opposite concepts. The law of included infinitely-many-middles suggests that between opposites, there exist infinitely many nuances or middle values. Sorites' paradoxes challenge traditional logic by exposing the difficulties in defining vague boundaries. Neutrosophic Interpretation suggests introducing a buffer zone between opposites, resulting in Neutrosophic Sorites Paradoxes. Moreover, this exploration highlights the need for a more flexible and nuanced understanding of conceptual boundaries, acknowledging the dynamic and indeterminate nature of many philosophical and logical constructs. Finally, we delve into the application of neutrosophy to various cultural and philosophical concepts. The legendary figure of Gilgamesh, described as two-thirds god and one-third human, is examined through both traditional and neutrosophic perspectives. Additionally, Hindu concepts of Dharma, Adharma, and Karma are reexamined within the context of neutrosophy. The logic of the Diamond Sutra in Mahayana Buddhism, characterized by paradoxical language and a focus on emptiness, aligns with neutrosophic principles in challenging fixed notions and embracing the interconnected and indeterminate aspects of reality. Despite diverse cultural origins, these examples share a common thread in questioning absolutes and embracing the dynamic nature of existence.